La disponibilidad de apoyo social en la vejez: sumando vínculos y dispositivos - Josefina Arias, Claudia (2023)
The study of human aging has become an unavoidable topic on the public agenda worldwide. The population aging poses new challenges and demands that will require changes and readjustments in formal and informal social support for the elderly. In a context characterized by the emergence of new needs and demands, the strengthening and articulation of supports is very important. Indeed, these actions are essential when it comes to providing the appropriate responses to the various situations that older people go through, according to their needs and resources, both personal and community. International organizations interested in old age and aging have highlighted their importance and the need for governments to develop policies that promote and guarantee access to them. This article defines and exemplifies formal and informal supports and provides a brief description of each of the parts and articles that make up this special issue of the magazine. It is intended to address the supports available to older people who attend educational workshops, centers and day clubs and who live in long-term residences from the perspective of three participants involved: the elderly, their families and the professionals who work in them. The generation of knowledge about the informal and formal support resources available to them, both for daily life and for coping with situations of change and loss, will enable the development of practices aimed at improving their living conditions and promoting integral wellness.